Mainstreaming One Health competencies into higher education institutions - Tiku, S.; Olijira, L.; Yadeta, W.; Tadesse, Yordanos; Mor, Siobhan M.; Mutua, Florence K.; Richards, Shauna; Kaba, Mirgissa (International Livestock Research Institute, 2024)
Over the past decade, the world has faced severe public health threats including zoonotic diseases, food insecurity, antimicrobial resistance and other emerging pandemic threats. This has been attributed to factors such as climate change, globalization, agricultural intensification, increased human population, leading to pressure on land resources, increased global trade and travel and increased use of antimicrobials in animal production and food preservation. One Health, an integrated, unifying approach that aims to sustainably balance and optimize the health of people, animals and ecosystems has been identified as an effective way to fight these threats at the human–animal–environment interface. One Health education creates a workforce, equipped with knowledge, skills and positive attitude to prevent, detect and respond to infectious disease threats, capable of fostering cross sectoral and interdisciplinary collaboration.